Morphological and physiological development of auditory synapses - Yu, Wei-Ming (2014)
Acoustic communication requires gathering, transforming, and interpreting diverse sound cues. To achieve this, all the spatial and temporal features of complex sound stimuli must be captured in the firing patterns of the primary sensory neurons and then accurately transmitted along auditory pathways for additional processing. The mammalian auditory system relies on several synapses with unique properties in order to meet this task: the auditory ribbon synapses, the endbulb of Held, and the calyx of Held. Each of these synapses develops morphological and electrophysiological characteristics that enable the remarkably precise signal transmission necessary for conveying the miniscule differences in timing that underly sound localization. In this article, we review the current knowledge of how these synapses develop and mature to acquire the specialized features necessary for the sense of hearing.